The Impact of Business Diagnostics on the Activities of SMEs in Nigeria - Aladejebi, Olufemi; Peter, Bamkole; Amao-Taiwo, Bukola (Archives of Business Research, 2024)
In the context of Nigeria, where the average lifespan of businesses is limited to approximately five years, addressing and overcoming challenges has become a critical imperative. This study underscores the pivotal role of business diagnostics in supporting the growth and sustainability of businesses, particularly Small and Medium Enterprises (SMEs), in Nigeria. Specifically, it investigates how SMEs in Nigeria employ diagnostic tools, such as SWOT analysis, to discern their strengths, weaknesses, opportunities, and threats. Utilizing a qualitative research methodology, the study employs a structured, open-ended questionnaire as the primary data collection instrument, with a sample of fifteen strategically chosen SMEs participating in a specialized course at a business school. Purposive sampling ensures diversity among the selected SMEs, enriching the depth of the collected data. The structured, open-ended questionnaire allows participants to express their perspectives, facilitating in-depth responses freely. Thematic analysis is applied to identify patterns and insights within the qualitative data, providing nuanced answers to the research questions. The findings underscore that business diagnostics significantly contribute to the effective management and growth of SMEs in Nigeria, illuminating the potential for increased economic development through improved SME performance. Incorporating the results, the study sheds light on the varied experiences and perspectives of SMEs with business diagnostics, offering a rich and contextualized exploration of the subject matter. Meaningful recommendations derived from the study’s findings, contribute to the body of knowledge on effective business diagnostics for SMEs in Nigeria.